Analisis Kualitas Instrumen Tes Hasil Belajar Pembelajaran IPAS pada Kemampuan Literasi Sains dan Berpikir Kritis Siswa - Diah Susilowati (Perkumpulan Kualitama Edukatika Indonesia, 2023)
Instruments that are used in measuring student learning outcomes, especially science learning in the competency skills of scientific literacy and critical thinking skills in elementary school students must have adequate quality and eligibility. This study aimed to determine the quality and validity of the science achievement test instrument for class IV SD in learning materials Plants, the Source of Life on earth based on content validity tests. The research includes a quantitative descriptive approach with research subjects namely lecturers, class members, as well as class IV students at SDN 01 Wanurejan. Determining the validity of using the Aiken index to measure the level of validity of each question item. The results of the study show that the analysis of a score of 30 <n ? 50 is in the very good category, so the instrument as a whole has very good content validity, and can be used with a little revision. Meanwhile, the Aiken's index validity test obtained 2 items in the medium validity category and 8 items in the high validity category. Thus, overall the learning outcomes test instrument has good quality and validity so that it is suitable for use in measuring science learning, especially in the aspects of scientific literacy and critical thinking skills.